Return to the heart of darkness - Koppel, Ted, 1940 Feb. 8-; Wooten, James T.; ABC News Productions; Films for the Humanities (Firm) (Princeton, N.J. : Films for the Humanities & Sciences, 2006)
Examines new challenges in central and eastern Africa, reporting on the instability created by Hutu guerillas known as the FDLR. Also analyzes successes and failures that have occurred as Rwanda tries to heal. Revisiting the shores of Lake Kivu, where vast numbers of refugees died during the violence of the mid-1990s, this program studies the efforts of the International Crisis Group to address vestiges of the tragedy and remove the FDLR -- giving the world a second chance to pay attention.
Originally aired on Oct. 26, 2005 on Nightline.
Streaming video.
Hosted by Ted Koppel ; correspondent, Jim Wooten.
Electronic reproduction.
Mode of access: World Wide Web.
System requirements: Macintosh PC; Mac OS X with Safari 1.0 or higher; Firefox for Macintosh 1.0.4 or higher; QuickTime Player 6.0 or higher.
Keywords: Migration, Internal -- Congo (Democratic Republic); Political violence -- Congo (Democratic Republic); Refugees -- Congo (Democratic Republic); Congo (Democratic Republic) -- Ethnic relations; Congo (Democratic Republic) -- History -- 1997-; Congo (Democratic Republic) -- Social conditions